2015
DOI: 10.4310/hha.2015.v17.n2.a15
|View full text |Cite
|
Sign up to set email alerts
|

Lin–Wang type formula for the Haefliger invariant

Abstract: In this paper we study the Haefliger invariant for long embeddings R 4k−1 ֒→ R 6k in terms of the self-intersections of their projections to R 6k−1 , under the condition that the projection is a generic long immersion R 4k−1 R 6k−1 . We define the notion of "crossing changes" of the embeddings at the self-intersections and describe the change of the isotopy classes under crossing changes using the linking numbers of the double point sets in R 4k−1 . This formula is a higher-dimensional analogue to that of X.-S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Theorem 8.1 [23,Theorem B]. For any 𝑑 ⩾ 3 and 𝑛 ⩾ 1, the lowest non-vanishing homotopy group of the layer 𝖥 𝑛+1 (𝑀) in the Taylor tower for Emb 𝜕 (𝔻 1 , 𝑀) admits an isomorphism (32) We first make a few remarks on the objects that appear in the statement. Firstly, 𝖫𝗂𝖾 𝜋 1 𝑀 (𝑛) is the group of decorated Lie trees from Section 3.5.…”
Section: A Recollectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Theorem 8.1 [23,Theorem B]. For any 𝑑 ⩾ 3 and 𝑛 ⩾ 1, the lowest non-vanishing homotopy group of the layer 𝖥 𝑛+1 (𝑀) in the Taylor tower for Emb 𝜕 (𝔻 1 , 𝑀) admits an isomorphism (32) We first make a few remarks on the objects that appear in the statement. Firstly, 𝖫𝗂𝖾 𝜋 1 𝑀 (𝑛) is the group of decorated Lie trees from Section 3.5.…”
Section: A Recollectionmentioning
confidence: 99%
“…Haefliger first used this link in the case 𝑑 = 6𝑘 and 𝑝 = 𝑞 = 4𝑘 − 1 in order to construct a generator of Emb(𝕊 4𝑘−1 , 𝕊 6𝑘 ) or Emb 𝜕 ( 𝔻 4𝑘−1 , 𝔻 6𝑘 ) , by an ambient connect sum analogous to the one for the classical trefoil. Sakai [32] defined finite-type invariants of such knots and showed that the Haefliger trefoil is detected by a type 2 invariant; an invariant can be defined by foliating by arcs and then taking 𝖾𝗏 2 ∶ 𝜋 4𝑘−2 Emb 𝜕 (𝔻 1 , 𝔻 2𝑘+2 ) → ℤ, see (7).…”
Section: About the Haefliger Trefoilmentioning
confidence: 99%
See 1 more Smart Citation